Worldwide Presence and Features of Flea-Borne Rickettsia asembonensis - Maina, Alice N.; Jiang, Ju; Luce-Fedrow, Alison; St. John, Heidi K.; Farris, Christina M.; Richards, Allen L. (Frontiers in Veterinary Science, 2019)
Rickettsia asembonensis, the most well characterized rickettsia of the Rickettsia felis-like organisms (RFLO), is relatively unknown within the vector-borne diseases research community. The agent was initially identified in peri-domestic fleas from Asembo, Kenya in an area in which Rickettsia felis was associated with fever patients. Local fleas collected from domestic animals and within homes were predominately infected with R. asembonensis with less than 10% infected with R. felis. Since the identification of R. asembonensis in Kenya, it has been reported in other locations within Africa, Asia, the Middle East, Europe, North America, and South America. Interest has been building on the potential of R. asembonensis in infecting vertebrate hosts including humans, non-human primates, dogs, and other animals. The current knowledge of the presence, prevalence and distribution of R. asembonensis worldwide, as well as its arthropod hosts and potential as a pathogen are discussed in this manuscript.